Effect of Multilayers CdS Nanocrystalline Thin Films on the Performance of Dye-Sensitized Solar Cells - Abdullah A. Hussain; Haider Abdulelah; Ali H. Amteghy; Raed A. Dheyab; Ban Hamdan AlMulla (Journal of Nanotechnology)
Due to relatively low price and nontoxicity of photovoltaic (PV) systems, dye-sensitized solar cells (DSSCs) recently gained a lot of attention in terms of improving their performance and longevity. Because most of the major elements are impacted by their separate production and layering procedures, the substances in DSSCs are critical to achieving these goals. Methylene blue dye sensitizer-based solar cells were effectively constructed in this work, and DSSC performance was assessed. The morphologies of nanocrystalline CdS thin films were investigated by the FE-SEM machine, and then XRD patterns of 1 layer, 2 layers, and 3 layers of nanocrystalline CdS thin films were analyzed. The thicknesses of the prepared samples were about 391 nm, 457 nm, and 912 nm for 1, 2, and 3 layers of nanocrystalline CdS thin film, respectively. J-V characteristics of the multilayer CdS thin films have been studied under a 100 mW/cm2 sunlight source. The experimental results revealed that the highest power conversion efficiency of a 3 layer porous-nanowall CdS/MB device was about 0.47%.